214 Errors in Medication Prescriptions in Paediatric Intensive Care Patients. (October 2012) - Maat, B; Bollen, CW; Vught, AJ van; Egberts, ACG; Rademaker, CMA
Abstract : Background and aims: Prescribing errors frequently occur in paediatric medicine, especially in paediatric intensive care units (PICUs). Computerized physician order entry (CPOE) systems may help to prevent these errors. This study examined the frequency, nature and determinants of prescribing errors in electronic and handwritten prescriptions in a PICU population. Methods: All prescriptions (electronic and handwritten) for children aged 0–18 years hospitalized in a 14-bed PICU of a university medical center, The Netherlands, from February 2008 - December 2010, were prospectively collected and checked for prescribing errors and determinants (prescription-, patient- and medication-related) thereof. Results: 23, 207 prescriptions for 659 patients were collected, of which 14, 887 (64%) were handwritten and 8, 312 (36%) electronically ordered. 6% of the prescriptions contained a therapeutic error and 54% was administratively incomplete (1–7 missing items per prescription). Electronically ordered prescriptions contained significantly less therapeutic and administrative errors than handwritten prescriptions (p<0.001), mainly due to better legibility and completeness. More than 10% of the prescribed doses was outside the therapeutic range of the Dutch paediatric drug formulary. Important determinants of prescribing errors were handwritten prescriptions (OR=3.1 [2.9–3.3]), intravenous medication (OR=2.9 [2.6–3.3]), the youngest of age (up to 1 month OR=1.2 [1.1–1.4] and drugs affecting the musculo-skeletal system (OR=3.4 [2.9–3.9]). Conclusions: PICU prescribing errors occur frequently. CPOE systems reduce error rates but do not fully prevent these. Data to support what is exactly needed to build better prescribing systems for PICU patients are scarce. This study provides information for improvements in electronic prescribing for PICU patients.